Alteration in Auxin Homeostasis and Signaling by Overexpression Of PINOID Kinase Causes Leaf Growth Defects in Arabidopsis thaliana - Saini, Kumud; Markakis, Marios N.; Zdanio, Malgorzata; Balcerowicz, Daria M.; Beeckman, Tom; De Veylder, Lieven; Prinsen, Els; Beemster, Gerrit T. S.; Vissenberg, Kris (Frontiers in Plant Science, 2017)
In plants many developmental processes are regulated by auxin and its directional transport. PINOID (PID) kinase helps to regulate this transport by influencing polar recruitment of PIN efflux proteins on the cellular membranes. We investigated how altered auxin levels affect leaf growth in Arabidopsis thaliana. Arabidopsis mutants with altered PID expression levels were used to study the effect on auxin distribution and leaf development. Single knockouts showed small pleiotropic growth defects. Contrastingly, several leaf phenotypes related to changes in auxin concentrations and transcriptional activity were observed in PID overexpression (PIDOE) lines. Unlike in the knockout lines, the leaves of PIDOE lines showed an elevation in total indole-3-acetic acid (IAA). Accordingly, enhanced DR5-visualized auxin responses were detected, especially along the leaf margins. Kinematic analysis revealed that ectopic expression of PID negatively affects cell proliferation and expansion rates, yielding reduced cell numbers and small-sized cells in the PIDOE leaves. We used PIDOE lines as a tool to study auxin dose effects on leaf development and demonstrate that auxin, above a certain threshold, has a negative affect on leaf growth. RNA sequencing further showed how subtle PIDOE-related changes in auxin levels lead to transcriptional reprogramming of cellular processes.